The BMI MEASUREMENT TRAINING IN THE FEMALE YOUNG COMMUNITY IN SAMARINDA CITY - Fransiska Novita; Maria Floriana Ping (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2025)
Introduction: Body Mass Index (BMI) is a crucial factor for adolescent girls. This is related to efforts to prevent stunting in the future when they become mothers. Early detection can be done independently by adolescent girls by monitoring their nutritional status based on BMI. Objective: To train adolescent girls' ability to measure BMI in Samarinda City. Method: This activity will be implemented in two sessions. The first session will measure height and weight. This will then be followed by practice calculating BMI. Results and Conclusions: Participants were categorized as early and middle adolescents. All participants took BMI measurements. The BMI measurement results found that 31.35% of adolescents were undernourished and 4.07% were overnourished. Continuous early detection of BMI is necessary to monitor adolescent nutritional status.Keywords: BMI measurement, adolescent girls